Ensiling Legume with Cereal Fodder Influences Quality of Silage Mixtures - Goyal, Meenakshi; Tiwana, U.S. (Indian Journal of Animal Nutrition, 2018)
This study was conducted to determine the fermentation characteristics and nutritive value of corn (Zea mays L.) + cow pea (Vigna ungiculata L.) and oats (Avena sativa L.) + alfalfa (Medicago sativa L.) silages. The corn-cowpea and oats-alfalfa mixtures were ensiled separately in the ratio of 100: 0 (A), 75: 25 (B), 50: 50 (C), 25: 75 (D) and 0: 100 (E) of grass and legume in each case. The fodder mixtures were ensiled in vacuumed plastic bags for 45 days at room temperature. The addition of cowpea in corn or alfalfa in oats had significant effect (P<0.05) on chemical composition, pH value, NH3-N and total digestible nutrients of silage mixtures. The levels of crude protein, ash content, pH value and NH3-N were higher (P<0.05) in silage mixtures with increased proportion of legumes. Acid detergent fibre and neutral detergent fibre contents were, however, high in silage mixture with increased proportion of corn or oats. Fermentation characteristics improved in corn-cowpea and oats-alfalfa mixture silages at a ratio of 75: 25 compared with the other combinations.